Dispersion of Particulate Matter from Palm Oil Refinery Mill - Wong, Lee Ing (2006)
The appearance of industrial emissions and the degradation of scenic vistas are two characteristics of air pollution that humans object. Reduction in visibility suggests worsening pollution levels. Visibility is characterized by either its visual range, or by opacity. The emissions from mobile source and stationary source are the major source of air pollutions contribution in Malaysia. Suspended particulate matter (SPM) and nitrogen dioxide (NO2) are the predominant pollutants from these two sources exhaust smokes. Increasing the amounts of combustion product, gases carbon dioxide (CO2) in the atmosphere also create an effect of blanket layer to increase retention of particulate matter and vapour near the earth before releasing to the space. The consequence of increasing the concentration, the particulate matter dissolves with vapour and grows into droplets when the humidity exceeds approximately 70%. The saturated particulate matter acts as nuclei to scatter sun rays that will impair visibility and causing opaque situation know as haze. The study of dispersion particulate matter from palm oil mill serves as a purpose of modeling the transport of particulate matter for obtaining permits and prevention of significant deterioration (PSD) to the environment. Gaussian Plume Model from a point source, subject to various atmospheric conditions is used to calculate particulate matter concentration then display the distribution of plume dispersion using geographic information system (GIS). Mixing height is determined to forecast potential haze occurrence. Dispersion of particulate matter from palm oil mill is following Gaussian Model and its concentration is normally distributed. The calculated particulate matter concentration is evaluated using Transilient Matrix function. Atmospheric Stability, mixing height, wind direction, wind speed, natural and artificial features play an important role in dispersion process. High concentration area exhibits immediately under prevailing wind direction.